Group cognitive behavioural therapy can reduce stigma and improve treatment compliance in major depressive disorder patients. Issue 2 (2nd July 2019) - Tong, Ping; Bu, Ping; Yang, Yang; Dong, Liping; Sun, Ting; Shi, Yuanhong
Abstract: Aim: The stigma of mental disorders and poor treatment compliance can deprive patients with major depressive disorder (MDD) of receiving standard treatment. This study aimed to clarify whether MDD patients' stigma and treatment non‐compliance issues can be mitigated using group cognitive behavioural therapy (GCBT). Methods: Eighty‐eight participants with first‐episode MDD were randomly divided into GCBT groups (GCBTs) and control groups (Cs). The Hamilton Rating Scale for Depression (HRSD‐24), Morisky Medication Adherence Scale (MMAS‐8™) and Stigma Scale (SS) were used to evaluate the therapeutic effect on all participants before and after receiving GCBT. Data were assessed at baseline and post‐treatment. Results: At the baseline, there were no significant differences (in terms of the demographic data of the participants and the scores on HRSD‐24, MMAS‐8™ and SS) between the two groups. After 8 weeks of GCBT, there were significant differences in HRSD‐24 ( P < .01), MMAS‐8™ ( P < .01), SS ( P < .01), treatment compliance ( P < .01) and therapeutic effect evaluation based on rate of deduction ( P < .05) between the two groups. Conclusion: GCBT can reduce patients' sense of stigma, improve treatment compliance, effectively alleviate depressive symptoms and promote the recovery of MDD patients.